Enhancing Student Learning Motivation: A Problem-Based Learning Approach with Flipped Classroom Model in Distance Learning Design - Setiawan, M. Eval; Laswadi, Laswadi; Hermawan, Candra; Purnawati, Wilda (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2023)
This research aims to increase students’ learning motivation by developing a Problem-Based Learning learning design using the flipped classroom model. This research uses an approach that is part of non-experimental quantitative research. The sampling technique used purposive sampling. This research was measured using a learning motivation observation sheet in the form of a motivation rubric. Increased motivation was analysed based on a questionnaire based on the ARCS rubric. This research shows increased motivation in the learning process with the flipped classroom model and problem-based learning design. At the attention stage, there was an increase in student motivation by 13% from the first meeting to the second meeting and a rise of 6% from the second meeting to the third meeting. In the relevance aspect, there was an increase of 26% from meeting one to meeting two and 3% from meeting two to meeting three. Then, part of confidence, from the first to the second meeting, there was an increase of 9%, and from the second to the third meeting, it increased by 10%. Finally, in the aspect of satisfaction from meeting one to meeting two, there was an increase of 9%. Moreover, from meeting two to meeting three, there was an increase of 12%. It was concluded that the average increase in student motivation from the first lesson to the third lesson was 3% to 13%. In the future, further attention is needed on the affective and psychomotor aspects.